Is kidney disease associated with both Alzheimer's disease and vascular dementia?: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Basit, Saima; Damholt, Mette Brimnes; Wohlfahrt, Jan; Boyd, Heather A
Abstract: Background: Previous studies have found associations between renal dysfunction and cognitive impairment. Associations between kidney disease and dementia are less well‐established and the available evidence for associations with dementia subtypes is conflicting. Method: Our study cohort included 4, 320, 824 individuals ≥40 years of age and living in Denmark at some point during 1996‐2017. Of these, 123, 269 persons developed dementia during 60, 043, 110 person‐years of follow‐up (median follow‐up time, 14.8 years). We compared the risks of dementia in persons with and without a history of kidney disease using Cox regression with age as underlying time scale. All analyses were adjusted for sex, birth year, cardiovascular disease, autoimmune diseases, diabetes and hypertension. Result: Compared with persons without kidney disease, persons with any kidney disease had a higher risk of dementia overall (hazard ratio [HR] 1.22, 95% confidence interval [CI] 1.19‐1.25) and of early‐onset (<65 years) dementia in particular (HR 1.66, 95% CI 1.50‐1.85). Stronger associations were observed for acute kidney disease (dementia overall: HR 1.45, 95% CI 1.38‐1.52; early‐onset dementia: HR 2.12, 95% CI 1.70‐2.63; late‐onset dementia: HR 1.44, 95% CI 1.36‐1.52) than for chronic kidney disease (dementia overall: HR 1.15, 95% CI 1.10‐1.20; early‐onset dementia: HR 1.49, 95% CI 1.24‐1.78; late‐onset dementia(≥65 years): HR 1.15, 95% CI 1.11‐1.19). Persons with kidney disease had increased risks of vascular dementia (HR 1.43, 95% CI 1.33‐1.54) and other/unspecified dementia (HR 1.30, 95% CI 1.26‐1.34); in contrast, kidney disease was not associated with the risk of Alzheimer's disease (HR 0.98, 95% CI 0.94‐1.03). The magnitude of the association with vascular dementia overall was similar for acute kidney disease (HR 1.57, 95% CI 1.33‐1.86) and chronic kidney disease (HR 1.44, 95% CI 1.28‐1.63). However, acute kidney disease was very strongly associated with the risk of early‐onset vascular dementia (HR 3.09, 95% CI 1.65‐5.81). Conclusion: Kidney disease, especially acute kidney disease, was associated with increased risks of dementia, early‐onset dementia in particular. Kidney disease was associated with increased risks of vascular dementia but not of Alzheimer's disease.